Integration and Interconnection of Islam and Science to Strengthen the Islamic Education Curriculum - Safna Febriyani; Haris Riadi; Betti Fariati (LPPM Institut Pendidikan Nusantara Global, 2026)
The Islamic Religious Education (PAI) curriculum plays a strategic role in shaping students who are not only religiously devout but also scientifically literate and responsive to the dynamics of modern civilization. The integration and interconnection between Islam and science serves as a crucial paradigm for strengthening the PAI curriculum, preventing the dichotomy between religious and scientific knowledge. This study aims to examine the concept of Islamic–scientific integration and interconnection and its implications for reinforcing the PAI curriculum in the modern era. This research employs a library research method with a descriptive-analytical approach. The findings indicate that the integration of Islam and science positions revelation (the Qur'an and Hadith) as the primary source of knowledge that aligns with the empirical findings of modern science. This approach enriches the PAI curriculum by harmoniously linking spiritual, moral, and rational values, making Islamic education more contextual, relevant, and meaningful. Therefore, strengthening the PAI curriculum through the integration and interconnection of Islam and science can foster a generation that is religiously grounded, intellectually critical, and scientifically insightful, ready to face the challenges of the era of artificial intelligence and globalization.